Selected anthropometric measurements of children with autism and mental retardation - Layug, Kathryn Faye P. (2005)
Data were obtained by measuring weight, height, sitting height, chest and arm girths and BMI to determine the body composition and anthropometric profile of children with autism and MR in special private and public schools. Results showed that more children with autism are overweight than children with MR. 17 percent of the respondents were classified as above normal in weight. Most of the age groups had a normal mean height and sitting height except the twelve year - old age group who had an alarmingly below average classification. Chest and arm girth measurements present a pattern that follows a fairly normal growth curve, adhering to steady increases with age. 71 percent of the respondents had body mass indices that were classified as overweight.